2021
DOI: 10.18632/aging.202608
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA RHOT1 promotes progression and inhibits ferroptosis via mir-106a-5p/STAT3 axis in breast cancer

Abstract: To explore the effect of circRHOT1 on breast cancer progression and the underlying mechanism. Significantly, our data revealed that the depletion of circRHOT1 was able to repress the proliferation and induce the apoptosis of breast cancer cells. CircRHOT1 knockdown could remarkably inhibit the invasion and migration in the breast cancer cells. Meanwhile, the depletion of circRHOT1 enhanced the erastin-induced inhibition effect on cell growth of breast cancer cells. The circRHOT1 knockdown notably increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 27 publications
1
61
0
Order By: Relevance
“…Moreover, apoptosis and ferroptosis are both crucial phenotypes during cancer development. As several previous reports ( 19 , 25 27 ), silencing the circ_0067934 not only induces cell ferroptosis but also causes cell apoptosis. The authors should distinguish which is the main cause of the observed cell death in future investigations, despite it is difficult and complicated.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, apoptosis and ferroptosis are both crucial phenotypes during cancer development. As several previous reports ( 19 , 25 27 ), silencing the circ_0067934 not only induces cell ferroptosis but also causes cell apoptosis. The authors should distinguish which is the main cause of the observed cell death in future investigations, despite it is difficult and complicated.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, circ_0110757 was reported to increase temozolomide resistance in neuroblastoma via sponging miRNA-1298-5p [ 25 ]. Circular RNA RHOT1 promoted metastasis and suppressed ferroptosis via the miR-106a-5p/STAT3 axis in breast cancer [ 26 ]. Previously, circ_0005909 was shown to sponge miRNA-338-3p and miR-936 in osteosarcoma, thus promoting the progression of osteosarcoma [ 13 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… Wu et al (2020) concluded that the overexpression of glycogen synthase kinase-3β enhanced the therapeutic effect of erastin-triggered ferroptosis in breast tumors. Besides, Zhang et al (2021) found that circRHOT1-induced ferroptosis could be inhibited by the upregulation of STAT3 and miR-106a-5p in breast cancer. It is necessary to find more valuable targets and make rational use of targeted drugs to trigger ferroptosis, thereby enhancing the sensitivity of anti-tumor drugs in breast cancer.…”
Section: Ferroptosis In Relevant Malignant Tumorsmentioning
confidence: 98%